2021
DOI: 10.1038/s41598-021-81624-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic DMI-free skyrmion formation and robust dynamic behaviors in magnetic hemispherical shells

Abstract: We performed finite-element micromagnetic simulations to examine the formation of skyrmions without intrinsic Dzyaloshinskii–Moriya interaction (DMI) in magnetic hemispherical shells. We found that curvature-induced DM-like interaction allows for further stabilization of skyrmions without the DMI in curved-geometry hemispherical shells for a specific range of uniaxial perpendicular magnetic anisotropy (PMA) constant Ku. The larger the curvature of the shell, the higher the Ku value required for the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Furthermore, the successful synthesis of 2D magnets provides a promising platform to study the Dzyaloshinskii-Moriya interaction (DMI) [13][14][15] . DMI, an antisymmetric exchange interaction between two magnetic atoms within one surface layer 16,17 , originates from spin-orbit coupling (SOC) and competes with the perpendicular magnetic anisotropy and the Heisenberg exchange coupling to generate the chiral magnetic structures like the chiral domain walls, helical spins, and skyrmions [18][19][20] . These chiral magnetic structure possess great application potential in next-generation memory devices 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the successful synthesis of 2D magnets provides a promising platform to study the Dzyaloshinskii-Moriya interaction (DMI) [13][14][15] . DMI, an antisymmetric exchange interaction between two magnetic atoms within one surface layer 16,17 , originates from spin-orbit coupling (SOC) and competes with the perpendicular magnetic anisotropy and the Heisenberg exchange coupling to generate the chiral magnetic structures like the chiral domain walls, helical spins, and skyrmions [18][19][20] . These chiral magnetic structure possess great application potential in next-generation memory devices 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the other two possible core polarity–chirality combinations have not been obtained in micromagnetic simulations under the same conditions. We have found that they can be stabilized by, for example, introducing additional radial 27 or perpendicular 26 magnetic anisotropy (see Sect. 2 of the “ Supplementary Information ”, where a magnetization configuration with P*C = − 1 is presented).…”
Section: Resultsmentioning
confidence: 97%
“…The article 20 reports the formation of skyrmion states in soft hemi-ellipsoidal particles, but at non-zero applied magnetic fields, while Refs. 26 , 27 report them in hemispheres at zero field but with an additional magnetic anisotropy. Here we demonstrate the possibility to observe 3D quasi-skyrmions in both cylindrical and dome-shaped thick nanodots with no need of special magnetic material, i.e., with no DMI and no out-of-plane anisotropy, in particular, in ultra soft Permalloy nanostructures with radius ca.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations